Relationship difficulties and "technoference" during the COVID-19 pandemic. (November 2022) - Zoppolat, Giulia; Righetti, Francesca; Balzarini, Rhonda N.; Alonso-Ferres, María; Urganci, Betul; Rodrigues, David L.; Debrot, Anik; Wiwattanapantuwong, Juthatip; Dharma, Christoffer; Chi, Peilian; Karremans, Johan C.; Schoebi, Dominik; et al.
The COVID-19 pandemic has touched many aspects of people's lives around the world, including their romantic relationships. While media outlets have reported that the pandemic is difficult for couples, empirical evidence is needed to test these claims and understand why this may be. In two highly powered studies ( N = 3271) using repeated measure and longitudinal approaches, we found that people who experienced COVID-19 related challenges (i.e., lockdown, reduced face-to-face interactions, boredom, or worry) also reported greater self and partner phone use (Study 1) and time spent on social media (Study 2), and subsequently experienced more conflict and less satisfaction in their romantic relationship. The findings provide insight into the struggles people faced in their relationships during the pandemic and suggest that the increase in screen time – a rising phenomenon due to the migration of many parts of life online – may be a challenge for couples.